Atomic‐Level Insight into the Formation of Subsurface Dislocation Layer and Its Effect on Mechanical Properties During Ultrafast Laser Micro/Nano Fabrication (Adv. Funct. Mater. 15/2022). (11th April 2022) - Xie, Jiawang; Yan, Jianfeng; Zhu, Dezhi; He, Guangzhi
Abstract : Atomic Structures In article number 2108802, Jianfeng Yan and co‐workers investigate the formation of the subsurface dislocation layer and its effect on mechanical properties during ultrafast laser fabrication at the atomic level. Three layers with different atomic structures, the recast layer, dislocation layer, and unaffected layer, are found after femtosecond laser irradiation. The subsurface dislocation layer is formed by laser‐induced stress waves, and the effect on the mechanical properties of the metal is studied.